Grass2Cash RHoMIS baseline survey in Ethiopia - Paul, Birthe K.; Tigabie, Abiro; Burkart, Stefan; Notenbaert, An Maria Omer (International Center for Tropical Agriculture, 2020)
This data was collected using the Rural Household Multi-Indicator Survey (RHoMIS) tool to a conduct baseline survey among 200 households in Ethiopia. The standard RHoMIS tool was extended with a feeding and forage module. The dataset can be used to understand agricultural productivity, food security, income, gender dynamics and livestock feeding and forage practice. (2020-02-06)